PENGARUH BAHAN PENSUSPENSI TERHADAP AKTIVITAS PENGAWET METIL PARABEN - A. Trihadi Kusuma (As-Syifaa Jurnal Farmasi, 2011)
AnalyzeQuality Of Cooking Oil With Double Fractination In Tidiness With The Recuring Usage.Have been research concerning quality of cooking oil double fractination in tidiness with the recuring usage by aims to determine quality of cooking oil with double fractination in tidiness with the recuring usage. The parameter of quality test of oil and fat is free fat acid number, saponification number, peroxide number, iodium number and water content with using titrimetri method. Kind of cooking oil which used were cooking oil double fractination. Research result show that cooking oil which used repeatedly with 3 times intensity has reduce of quality and no safe to consumed based on what standardized by National Standarization Agency.Key Words: methyl paraben, suspending agent,preservatif efectivity